Pengaruh Lingkungan Kerja dan Motivasi Intrinsik terhadap Kinerja Pegawai Bagian kesekretariat Dinas Perindustrian dan Perdagangan Provinsi Riau - Fransiska, Tria; Ibrahim, Restu; ', Marzolina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The research was conducted on Perindustrian and Perdagangan Provinsi Riau in order to determine how the Occupational and Environmental Effects of Intrinsic Motivation either simultaneously or partially The Secretariat of the Employee Performance On Perindustrian and Perdagangan Provinsi Riau. The variables in this study is: Work Environment and Intrinsic Motivation significant influence on employee performance parts secretariat On Perindustrian and Perdagangan Provinsi Riau and the dominant factor affecting the performance of employees is part of the secretariat of the Working Environment While the population in this study is part of the Secretariat employees on Perindustrian and Perdagangan Provinsi Riau which amounted to 38 people, with a total sample of 38 respondents. Multiple Linear Regression Analysis method by using SPSS version 17. Simultaneous regression (F test) showed that the independent studied (Work Environment and Intrinsic Motivation) together (simultaneously) have a significant effect on the dependent variable (employee performance). The magnitude of the effect that (R2) by the two independent variables together against the dependent variable, while the remaining is influenced by other variables not examined in this study. The results of the testing that has been done, the partial regression test (t test) showed that each of the independent variables studied (Work Environment and Intrinsic Motivation) has a significant effect on Perindustrian and Perdagangan Provinsi Riau the dependent variable (employee performance). Dominant variables affecting employee performance parts secretariat on is working environment where the value of t-counted highest compared with other independent variables. Recommendations to authors present is the agency needs to pay attention to the work environment and enhance intrinsic motivation for employees to improve employee performance in the future.Keywords: Work Environment, Intrinsic Motivation, Employee Performance